Part mass and shrinkage in micro injection moulding: statistical based optimisation using multiple quality criteria - Annicchiarico, Daniele; Attia, Usama M.; Alcock, Jeffrey R. (Elsevier Science B.V., Amsterdam., 2013)
Purpose: The aim of this paper is to optimise process conditions in micro injection moulding (m-IM) to minimise shrinkage whilst maximising part mass. Method: A Design of Experiment (DoE) approach was implemented for studying the effect of five processing parameters on shrinkage and part mass. A multiple quality criteria based analysis was used to optimise the process. Results: Significant factors were found for shrinkage and part mass. Conclusions: The multi quality criteria could be optimized, and this optimization validated experimentally.
Keywords: Part mass Shrinkage Micro injection moulding Optimization Multiple quality criteria